Faktor-Faktor Prediktor Perilaku Pembelian Emas di Pekanbaru - suci, afred (Komunitas Manajemen Kompetitif, 2016)
Abstract: The present research was conducted at Plaza Sukaramai Pekanbaru, aGoldSalesCenter in Pekanbaru. The study needs to find out the effect of product attribute, price and culture on the buying behaviors of the Pekanbaru consumers. The sample consisted of 160 buyers who were selected using the combination of cluster and purposive sampling technique. The variables are the product attribute, prices and culture as the independent variables, and the buying behavior as the dependent one. The data were analyzed using multiple regression analysis. The study reveals that product attribute has a positive and significant effect on the buying behavior. The price has a positive and significant effect on the buying behavior. Culture has a positive but insignificant effect on buying behavior. Keywords: Product Attribute, Price, Culture and Buying Behavior